Conformation of the Solute-Binding Protein AdcAII Influences Zinc Uptake in Streptococcus pneumoniae - Župan, Marina L.; Luo, Zhenyao; Ganio, Katherine; Pederick, Victoria G.; Neville, Stephanie L.; Deplazes, Evelyne; Kobe, Boštjan; McDevitt, Christopher A. (Frontiers in Cellular and Infection Microbiology, 2021)
Streptococcus pneumoniae scavenges essential zinc ions from the host during colonization and infection. This is achieved by the ATP-binding cassette transporter, AdcCB, and two solute-binding proteins (SBPs), AdcA and AdcAII. It has been established that AdcAII serves a greater role during initial infection, but the molecular details of how the protein selectively acquires Zn(II) remain poorly understood. This can be attributed to the refractory nature of metal-free AdcAII to high-resolution structural determination techniques. Here, we overcome this issue by separately mutating the Zn(II)-coordinating residues and performing a combination of structural and biochemical analyses on the variant proteins. Structural analyses of Zn(II)-bound AdcAII variants revealed that specific regions within the protein underwent conformational changes via direct coupling to each of the metal-binding residues. Quantitative in vitro metal-binding assays combined with affinity determination and phenotypic growth assays revealed that each of the four Zn(II)-coordinating residues contributes to metal binding by AdcAII. Intriguingly, the phenotypic growth impact of the mutant adcAII alleles was, in general, independent of affinity, suggesting that the Zn(II)-bound conformation of the SBP is crucial for efficacious metal uptake. Collectively, these data highlight the intimate coupling of ligand affinity with protein conformational change in ligand-receptor proteins and provide a putative mechanism for AdcAII. These findings provide further mechanistic insight into the structural and functional diversity of SBPs that is broadly applicable to other prokaryotes.